2001
DOI: 10.1029/2001ja900019
|View full text |Cite
|
Sign up to set email alerts
|

Are earthward bursty bulk flows convective or field‐aligned?

Abstract: Abstract. We use five years of Geotail and AMPTE/IRM measurements in the near-Earth magnetotail to compute angles between vectors of fast earthward plasma flow and the local magnetic field. In the low-fi parts of the magnetotail, fast flows were found to be nearly field-aligned with an average angle of --•20 ø. In the high-fi plasma sheet the average angle was larger than 45 ø. The existence of a substantial convective component in the plasma sheet confirms the importance of the bursty bulk flow phenomenon for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Depending on which plasma sheet regime is under consideration (CPS or PSBL), the axis orientation should vary between (quasi-) perpendicular and (quasi-) parallel to the magnetic field. The BBFs are dominantly (quasi-) perpendicular to the magnetic field in the CPS [Angelopoulos et al, 1994], and they are likely to extend into field-aligned beams in the PSBL [Nakamura et al, 1992;Petrukovich et al, 2001].…”
Section: Ecr Scale Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on which plasma sheet regime is under consideration (CPS or PSBL), the axis orientation should vary between (quasi-) perpendicular and (quasi-) parallel to the magnetic field. The BBFs are dominantly (quasi-) perpendicular to the magnetic field in the CPS [Angelopoulos et al, 1994], and they are likely to extend into field-aligned beams in the PSBL [Nakamura et al, 1992;Petrukovich et al, 2001].…”
Section: Ecr Scale Sizementioning
confidence: 99%
“…In the CPS, the high-speed flows are generally bulk flows which are (quasi-) perpendicular to the ambient magnetic field, with GSM V x being the dominant velocity component, and V y occasionally substantial [Angelopoulos et al, 1994]. In the PSBL, on the other hand, the high-speed flows can usually be characterized as field-aligned beams [Nakamura et al, 1992;Petrukovich et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…They tend to occur more frequently during active times but can occur also in the absence of substorms. The flows occur both in the high-beta central plasma sheet (beta is the ratio of plasma pressure over magnetic pressure), where they have a significant component perpendicular to the magnetic field, and in the low-beta plasma sheet boundary layer, where they are strongly field-aligned [e.g., Petrukovich et al, 2001]. These occurrences may be related to different activity phases, for instance, substorm expansion versus recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Satellite observations in the magnetotail [e.g., Baumjohann et al, 1990;Angelopoulos et al, 1992Angelopoulos et al, , 1994Sergeev et al, 1996;Schödel et al, 2001aSchödel et al, , 2001bPetrukovich et al, 2001] have demonstrated that the major transport of mass, energy, and magnetic flux in the plasma sheet occurs in a bursty fashion, associated with "bursty bulk flows" (BBFs). BBFs in the plasma sheet are fast flows (several hundreds of kilometers per second) of typically 10 minutes' total duration with individual peaks of the order of 1 minute [Angelopoulos et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…The observed fast flow in this event is perpendicular to the magnetic field. Fast flows can be both parallel and perpendicular to the magnetic field (Petrukoviclh et al, 2001;Raj et al, 2002). Perpendicular flows are typically found in high-β plasma, while parallel flows are found in low-β plasma.…”
Section: Discussionmentioning
confidence: 99%